Literary Studies and Well-Being Structures of Experience in the Worldly Work of Literature and Healthcare - Schleifer, Ronald (Bloomsbury Academic, 2022)
The literary arts represent and provoke experiences of understanding and emotion, and this open access study examines how the practical pursuit of well-being in healthcare reveals purposes at the core of our engagements with and understanding of literature itself. During the past twenty years, much admirable work in the "health humanities" has focused upon what studies of literature contribute to the understandings and the practical work-the "worldly work"-of healthcare. Such a project aims at developing healthcare practitioners who bring greater care to those who come to them ailing or in fear or faced with terrible suffering. Literary Studies and Well-Being turns this inside out by examining the intergenerational caretaking of healthcare in a manner which allows us to comprehend the nature and discipline of literary studies in new ways. The ebook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com. Open access was funded by The University of Oklahoma.